Soil phosphorus dynamics along a short‐term ecological restoration trajectory of a coastal sandplain forest in New Zealand. (27th October 2020) - Zhong, Hongtao; Smith, Carol; Robinson, Brett; Kim, Young‐Nam; Dickinson, Nicholas
Abstract: We aim to understand the impact of ecological restoration on soil biogeochemistry, and the interrelationship between vegetation and soil phosphorus. In a study of two different‐aged soils in coastal New Zealand, soils are described along a transition from abandoned agricultural pasture, through 6‐year old restoration plots, towards forest fragments that have been largely undisturbed for 75 and 166 years. Soil biogeochemistry varied spatially along this restoration trajectory; there were profound changes in surface soil, but little impact on deeper soil horizons. In the early stages, soil organic matter accumulation and decomposition, and increasing demand of N from fast‐growing plants corresponded with rapid nutrient mineralization. Loss of soil total P, an increase of occluded P, and the increasing importance of soil organic P as soils weathered and aged, supported conceptual models of longer‐term soil pedogenesis. There was no evidence that the success of the establishment of plants varied across the site, but this is a first report of vegetation establishment during ecological restoration markedly impacting soil P dynamics and biogeochemistry.